Pengaruh Pengetahuan, Sanksi dan Teknologi Perpajakan Terhadap Kepatuhan Wajib Pajak PPh Pasal 21 Tarif Efektif Rata-Rata dengan Kesadaran Pajak Sebagai Variabel Moderasi di Kota Makassar. - hartati haeruddin (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
The purpose of this study is to investigate the effects of tax knowledge, tax sanctions, and tax technology on the compliance of Makassar City taxpayers regarding. The 47,635 taxpayers who are registered. Tax Knowledge and Tax Sanctions factors significantly and favorably affect taxpayers' compliance with the Average Effective Rate under PPh 21 Income Tax, according to a partial test at multiple linear regression analysis. In the meantime, the Average Effective Rate compliance under PPh 21 Income Tax filers is not significantly impacted by the Tax Technology Variable. The link between Tax Knowledge, Tax Sanctions, and Tax Technology on the Compliance of Income Tax PPh 21 Average Effective Rate Taxpayers is not significantly impacted by the Tax Awareness Variable in the moderation regression analysis through direct effects.